Nigeria : Publication of Financial Sector Assessment Program Documentation -- Technical Note of Banking Cross-Border Issues. (IMF Staff Country Reports; Country Report, 2013)
The global financial crisis provided Nigerian banks with opportunities to expand within Sub-Saharan Africa. Nigerian banks have active cross-border liquidity flows, which may complicate the operation of monetary policy. The Central Bank of Nigeria (CBN) should enhance further its work in improving cross-border supervision, including home-host coordination and cooperation. The CBN may also consider taking initiative in establishing a regional coordination group similar to the Vienna Initiative. The CBN should improve data collection and granularity on cross-border transactions and funding flows of Nigerian international banks.